PENGARUH UMUR KEHAMILAN USIA REMAJA, PENGETAHUAN IBU TENTANG ANEMIA, DAN STATUS GIZI TERHADAP KEJADIAN ANEMIA DI KECAMATAN SAWAHAN KOTA SURABAYA - Pratiwi Hariyani Putri (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Pregnancy in adolescence has high enough of medical risk. Because in adolescence, their reproductive organs are not ripening enough to do its function. The effect of anemia in pregnancy, especially during adolescence age, can cause harm during pregnancy. The purpose of this research is to analyse the effect of gestational age, knowledge of mothers about pregnancy, and nutritional status on anemia in adolescence pregnancy in Sawahan District of Surabaya City. This research type was analitic observational. The research design used is case control design because the using of 2groups of cases, which are case and control group with 52 pregnant mother in each group. The result of this research which has been analyzed with double logistic regression, the variable which has significant score less than 0,05 among others: gestation pregnancy (p=0,000), It can be concludedthat pregnant mother in trimestry 3 have anemia probability 8,85 (1/0,113) times larger than pregnant mother in trimestry 2. There is influence of third trimester adolescence pregnancy to the occurrence of anemia.